The Effect of Rubber Tire Modification Training on the Speed of the Sickle Kick of Naga Kembar Pencak Silat Athletes of Pasangkayu District - Zulkifli Zulkifli; Didik Purwanto; Moh. Ihkal Sianto; Andi Saparia (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2026)
This study aims to determine the effect of tire modification training on increasing the speed of the sickle kick in Naga Kembar pencak silat athletes from Pasangkayu Regency. The method used was an experiment with a One-Group Pretest-Posttest Design. The research sample consisted of 20 athletes determined through a total sampling technique. The instrument used was a 15-second sickle kick speed test, adapted from the pencak silat sickle kick ability instrument developed by Kamarudin, Zulrafli, & Irma (2023). The intervention program was implemented for 15 meeting sessions with a frequency of three times per week for five weeks, lasting from April 11 to May 14, 2026. Data analysis used the Paired Sample T-Test assisted by JASP software. The results of the Shapiro-Wilk normality test showed a normal data distribution (pretest: p = 0.371; posttest: p = 0.775). The results of the hypothesis test showed a t value = -12.06, df = 19, and p < 0.001, so the null hypothesis was rejected. The average speed of the sickle kick increased from 17.25 to 20.80 (an increase of 20.58%), with Cohen's d = 2.696 which is included in the large effect category. The conclusion of this study is that tire rubber modification training has a significant effect on increasing the speed of the sickle kick of the Naga Kembar pencak silat athletes of Pasangkayu Regency and can be used as an economical alternative method for developing achievements at the regional level.